Accounting and Finance Innovations 2021
DOI: 10.5772/intechopen.99910
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Return and Risk of Cryptocurrency Bitcoin Asset as Investment Instrument

Abstract: This study aims to explore the potential use of the cryptocurrency bitcoin as an investment instrument in Indonesia. The return obtained from bitcoin cryptocurrency is compared to other investment instruments, namely stock returns, gold and the rupiah exchange rate. The research period was carried out based on research data from 2011 to 2020. This study employee compares means test (t test) and analysis of variance (F test) on rate of return of bitcoin investment. The bitcoin return compare to the rate of retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…The average difference between the two groups is 0.0934210 with a positive value, meaning that the cryptocurrency group has a higher mean E-ISSN: 2502-0633, P-ISSN: 2502-4647 http://jurnal.unissula.ac.id/index.php/ijibe DOI: http://dx.doi.org/10. 30659/ijibe.8.1.40-53 than the sharia stock group, this finding is in line with research from (Dasman, 2021;Liu & Tsyvinski, 2021;Troster et al, 2019).…”
Section: Return and Risk Difference Testsupporting
confidence: 89%
See 1 more Smart Citation
“…The average difference between the two groups is 0.0934210 with a positive value, meaning that the cryptocurrency group has a higher mean E-ISSN: 2502-0633, P-ISSN: 2502-4647 http://jurnal.unissula.ac.id/index.php/ijibe DOI: http://dx.doi.org/10. 30659/ijibe.8.1.40-53 than the sharia stock group, this finding is in line with research from (Dasman, 2021;Liu & Tsyvinski, 2021;Troster et al, 2019).…”
Section: Return and Risk Difference Testsupporting
confidence: 89%
“….000 a. Grouping Variable: market source: data processed 2022 Table 6 is the result of the different test for the risk variable, the Sig. (2-tailed) in the Mann Whitney test of 0.000 is smaller than 0.05 so that H0 is rejected and Ha is accepted, it means that there is a significant difference in the risk of cryptocurrencies and sharia stocks in line with research (Dasman, 2021;Jufridar et al, 2021;Liu & Tsyvinski, 2021).…”
Section: Return and Risk Difference Testsupporting
confidence: 54%
“…Ndlovu and Chikobvu (2022) concluded that BitCoin is riskier (highly volatile) than Rand using GARCH-GPD and recommended that BitCoin traders and investors should be cautious, especially when the market enters turbulent times. Their findings tally with that of Dasman (2021) who used a statistical tests approach in comparing the average returns and volatility of BitCoin against the Indonesian Composite Index, and gold. Also, the BitCoin average returns are significantly higher than the financial assets studied.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Based on Dasman (2021), the following equation is used to calculate the standard deviation of the daily return on cryptocurrencies:…”
Section: Stage Selection Of the Most Attractive Cryptocurrencies For ...mentioning
confidence: 99%